2010
DOI: 10.1159/000318009
|View full text |Cite
|
Sign up to set email alerts
|

Response to Dasatinib in a Patient with Concomitant Chronic Myeloid Leukemia and Chronic Lymphocytic Leukemia

Abstract: While chronic lymphocytic leukemia (CLL) and chronic myeloid leukemia (CML) are common diseases in the elderly, they rarely occur simultaneously in the same patient. Here we present the case of a 77-year-old patient diagnosed with CML in the chronic phase who showed an optimal response to 400 mg/day of imatinib. This patient progressed to Binet B-CLL with an 11q22.3 deletion and CD38 positivity in the 4th month of treatment. During the follow-up, his lymphocyte number doubled in <6 months. Based on previous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…27 The investigators concluded that increased rates of cancers were found at a very large range of sites and that immune deficiency, regardless of the mechanism of this deficiency, were responsible for the increased risk. There have also been scattered reports of coexistence of CML with other lymphoid malignancies such as CLL 28,29 and multiple myeloma. 30 In our analysis, the overall SIR of second cancers was 0.60 (95% CI, 0.44-0.81), suggesting a lower than expected rate of malignancies in patients treated with TKI, although the incidences of melanoma, endocrine tumors, kidney cancers, and CLL were higher than expected.…”
Section: Discussionmentioning
confidence: 99%
“…27 The investigators concluded that increased rates of cancers were found at a very large range of sites and that immune deficiency, regardless of the mechanism of this deficiency, were responsible for the increased risk. There have also been scattered reports of coexistence of CML with other lymphoid malignancies such as CLL 28,29 and multiple myeloma. 30 In our analysis, the overall SIR of second cancers was 0.60 (95% CI, 0.44-0.81), suggesting a lower than expected rate of malignancies in patients treated with TKI, although the incidences of melanoma, endocrine tumors, kidney cancers, and CLL were higher than expected.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of secondary solid neoplasms during the course of CLL includes carcinomas of the skin, stomach, colon, breast, or kidney [4, 5]; among secondary hematologic malignancies, cases of acute lymphocytic, myelocytic, monocytic and myelomonocytic leukemia, erythroleukemia, plasma cell leukaemia [6], and myeloproliferative neoplasms (MPN) have been reported [7–54].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most of the reported cases are purely anecdotal and merely descriptive. In a review of the literature, we found 25 cases of CLL/chronic myeloid leukemia (CML) [7–30], 18 cases of CLL/polycythemia vera (PV) [34, 35, 40–53], 12 cases of CLL/essential thrombocythemia (ET) [31–39], and only one case of CLL with primary myelofibrosis (PMF) [54].…”
Section: Introductionmentioning
confidence: 99%
“…To literature data, only 21 patients were diagnosed with CLL prior to CML or both simultaneously, and only in 6 patients were diagnosed prior CML to CLL [1][2][3][4][5][6][7]. Patients with diagnosis of CLL have predisposition for occurrence secondary malignancies because of impaired immune system or hemiotherapy [8].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to CLL, secondary malignancies are rare after CML [10,11]. CLL was occurred during the treatment of chronic phase of CML in five cases and during the accelerating phase of CML in one case [1,[3][4][5][6][7]. In all cases, CLL was appeared after 6-74 months after diagnosis of CML and patients were between 45 and 88 years old [7].…”
Section: Discussionmentioning
confidence: 99%